Fine mapping and characterization of RLL6 locus required for anti-silencing of a transgene and DNA demethylation in Arabidopsisthaliana - Wang, Xiangyu; Wang, Min; Dai, Jie; Wang, Qianqian; La, Honggui (Frontiers in Genetics, 2022)
DNA methylation patterns in plants are dynamically shaped by the antagonistic actions of DNA methylation and demethylation pathways. Although the DNA methylation pathway has been well studied, the DNA demethylation pathway, however, are not fully understood so far. To gain deeper insights into the mechanisms of DNA demethylation pathway, we conducted a genetic screening for proteins that were involved in preventing epigenetic gene silencing, and then the ones, which were also implicated in DNA demethylation pathway, were used for further studies. Eventually, a mutant with low luciferase luminescence (low LUC luminescence) was recovered, and named reduced LUC luminescence 6-1 (rll6-1). Map-based cloning revealed that rll6-1 mutation was located on chromosome 4, and there were a total of 10 candidate genes residing within such a region. Analyses of genome-wide methylation patterns of rll6-1 mutant showed that mutation of RLL6 locus led to 3863 hyper-DMRs (DMRs for differentially methylated regions) throughout five Arabidopsis chromosomes, and elevated DNA methylation level of 2×35S promoter, which was similar to that found in the ros1 (repressor of silencing 1) mutant. Further analysis demonstrated that there were 1456 common hyper-DMRs shared by rll6-1 and ros1-7 mutants, suggesting that both proteins acted together in a synergistic manner to remove DNA methylation. Further investigations demonstrated that mutation of RLL6 locus did not affect the expression of the four genes of the DNA glycosylase/lyase family. Thus, our results demonstrate that RLL6 locus-encoded protein not only participates in transcriptional anti-silencing of a transgene, but is also involved in DNA demethylation pathway.